Ethno-medical Botany and Some Biological Activities of Ipomoea oblongata collected in the Free State Province, South Africa - Semenya, Sebua Silas; Madamombe-Manduna, Idah; Mashele, Samson Sitheni; Polori, Ketlareng Liza (Journal of Biological Sciences, 2018)
Background and Objective: Literature reporting on the therapeutic uses and biological activities of Ipomoea oblongata (E.Mey.ex Choisy) is very scanty in South Africa. This study was carried out to comprehensively document medicinal use of this species and also determine some of its biological activities namely the antioxidant, total phenolic content and phytochemical properties. Materials and Methods: Ethnobotanical data on the healing applications of I. oblongata was gathered using a semi-structure questionnaire with 12 traditional healers (THs) practicing in the Free State province. The antioxidant properties and the total polyphenol content of I. oblongata extracts (Dichloromethane, DCM, Methanol, MeOH and Water, H2O) were determined by means of the 2, 2-Diphenylpicrylhydrazyl assay and the Folin Ciocalteu method, respectively. Gallic acid and ascorbic acid were used as standards.Phytochemical constituents were determined using standard screening procedures. Results: Roots of I. oblongata were mainly used by THs as remedy for ailments such as cancer, cardiovascular diseases, diarrhoea and nausea, inflammatory diseases, pregnancy and postnatal, respiratory infections, sexually transmitted infections and wounds. The MeOH roots extract of I. oblongata showed remarkable (98% at 0.25mg mLG1 and 99% at 0.5mg mLG1) antioxidant potential. Total phenolic contents of this species showed the Gallic acid equivalence (GAE) of 0.04 for both the MeOH and DCM and 0.03 for the H2O extract. The phytochemical screening exhibited the presence of carbohydrates, glycosides, steroids, terpenoids, alkaloids, flavonoids and tannis. Conclusion: Ipomoea oblongata roots are highly harvested and multi-used by THs against various human ailments, which could be attributed to the present of biologically active pharmaceutical components demonstrated.
Article published in the Journal of Biological Sciences; vol 18 (8): 441-449
Keywords: Antioxidants; Ethno-medicine; Ipomoea oblongata; Phytochemicals; Total phenolic content; Traditional healers; Medicinal plants--South Africa; Herbs-Therapeutic use